The hero Beowulf - Kimmel, Eric A. (Farrar, Straus and Giroux, 2005)
A simple, brief retelling of the Anglo-Saxon epic about the heroic efforts of Beowulf, son of Ecgtheow, to save the people of Heorot Hall from the terrible monster, Grendel. Annotation. The epic warrior from earliest English literature Beowulf was always a hero. As a child, he borrowed his father's sword to attack a nest of savage trolls that preyed on travelers. Now a young man, he seeks to defend the Danish king Hrothgar from a monster named Grendel. King Hrothgar asks Beowulf, "Are you not afraid?" Beowulf replies, "Why should I fear? If I am fated to win, then Grendel cannot defeat me. If I am fated to lose, then it has been my destiny since the day I was born." Sure of his role, if not of his success, Beowulf prepares to battle Grendel. This story of Beowulf is an introduction to the classic confrontation between good and evil, pared to perfection by the author and brought to life in monumental acrylic paintings by the artist.